A Comparative Study on Sentence Characters of Research Introductions by Indonesian Authors in Applied Linguistics - Ameitha Pratiwi; Safnil Arsyad; Syafryadin Syafryadin (Journal of Language and Literature, 2022)
This article presents the findings of sentence characters in article introductions written by Indonesian authors in Applied Linguistics published in national accredited and international reputable journals. This study aimed to identify sentence characters in article introductions used by Indonesian authors in Applied Linguistics published in national accredited journals and reputable international journals. The method employed in this study was a mixed-method to describe and compare the data. This study’s total number of articles was forty from eight different journals. The results indicated that the average sentence lengths in terms of words number per sentence in the international reputable journals articles were 22.38 words, and those in national accredited journals articles were 21.84 words. Also, the results revealed that the most commonly used sentence pattern in both groups of articles was complex sentences, with 414 sentences in national journals and 378 in international journals. It is followed by simple, compound-complex, and compound sentences. Therefore, it can be concluded that the Indonesian authors from both groups prefer to use long words and use complex sentences more often than the other sentence patterns. Hence, there is no important difference in sentence characters between national accredited and international reputable journals.